Health Care Reform in Greece : Progress and Reform Priorities - Kalavrezou, Niki (IMF Working Papers; Working Paper ;, 2021)
We review Greek public sector healthcare policies and health-related outcomes since 2010.We find that excess spending was successfully curtailed, elements of the institutional framework were modernized, and health outcomes have been relatively favorable. However, especially prior to Covid-19, public healthcare spending had been compressed to potentially unsustainable levels, with widening inequalities and large unmet needs, especially among the poor. Higher public spending and advancing structural healthcare reforms are needed to improve the efficiency and equity of the Greek healthcare system, including strengthening primary healthcare, reducing out-of-pocket payments, and eliminating remaining insurance gaps.